Virology : - Carter, John B. (John Wiley & Sons, 2007)
Virology: Principles and Applications is a clear and accessible introduction to this fast-moving field, providing a comprehensive resource enabling the reader to understand the key concepts surrounding this exciting subject. The reader is introduced to the principles of virus structure, replication and genetics, along with the theories behind the origins of viruses and how they are evolving. Taking a modern approach to the subject, the relevance of virology to everyday life is clearly emphasised and discussions of emerging viruses, cancer, vaccines, anti-viral drugs and gene vectors are included.